2021
DOI: 10.1001/jamainternmed.2021.0916
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intravenous Radiocontrast With Kidney Function

Abstract: IMPORTANCERadiocontrast has long been thought of as nephrotoxic; however, a number of recent observational studies found no evidence of an association between intravenous contrast and kidney injury. Because these studies are at high risk of confounding and selection bias, alternative study designs are required to enable more robust evaluation of this association.OBJECTIVE To determine whether intravenous radiocontrast exposure is associated with clinically significant long-term kidney impairment, using a study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 39 publications
2
18
1
2
Order By: Relevance
“…This might encourage physicians to subject patients more often to invasive management, following a discussion on the risk related to the procedure. Similar to these findings, Goulden et al 29 showed that contrast was not associated with increased risk of AKI or renal replacement therapy at 6 months using a regression discontinuity analysis in a quasiexperimental cohort study of 156 028 patients who underwent a computed tomography pulmonary embolism protocol. Alternatively, increased use of iso‐osmotic or low‐osmotic contrast in such patients may reduce the risk of AKI.…”
Section: Discussionmentioning
confidence: 68%
“…This might encourage physicians to subject patients more often to invasive management, following a discussion on the risk related to the procedure. Similar to these findings, Goulden et al 29 showed that contrast was not associated with increased risk of AKI or renal replacement therapy at 6 months using a regression discontinuity analysis in a quasiexperimental cohort study of 156 028 patients who underwent a computed tomography pulmonary embolism protocol. Alternatively, increased use of iso‐osmotic or low‐osmotic contrast in such patients may reduce the risk of AKI.…”
Section: Discussionmentioning
confidence: 68%
“…Although many RD designs can be used as a form of instrumental variable analysis, in which the threshold is used as an instrument in a "fuzzy RD" framework, we did not take this additional step in this analysis. 26,28 This is because the AMA cutoff can affect perinatal and maternal outcomes through multiple channels, some of which we were able to measure with our data and some we could not. Thus, an instrumental variable analysis would not necessarily meet the exclusion restriction for instrumental variable analysis, and estimates could be biased.…”
Section: Discussionmentioning
confidence: 91%
“…Regression discontinuity overcomes the issue of selection bias in comparing individuals with and without an intervention by exploiting an arbitrary cutoff in clinical decision-making rules or program eligibility, providing transparent visual evidence of changes in the outcome at the cutoff. [26][27][28][29] The RD method relies on the assumption that individuals within a narrow bandwidth around the cutoff have similar baseline characteristics other than the likelihood of receiving the We used local linear regression, with a binary indicator for age 35 years or older on the expected date of delivery as the main independent variable. Regressions controlled for the total number of days between the individual's 35th birthday and the expected date of delivery (the running variable), prepregnancy characteristics (ie, pregestational diabetes, chronic hypertension, obesity, and multiple gestation), zip code characteristics (percent Hispanic individuals, percent White individuals, median household income, and urbanicity), and county of residence characteristics (any hospital with a neonatal intensive care unit and OBGYNs per 10 000 deliveries), with fixed effects for state of residence, year, and month of delivery to improve precision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RD design is an increasingly used quasi-experimental design in healthcare and elsewhere to investigate the causal effects of interventions [13][14][15]. It has been described as the next-best evaluation method after a randomized controlled trial (RCT) [14], and its potential in healthcare to provide evidence on treatment effects is illustrated in several recent publications [20][21][22][23][24]. The RD design is attractive as it allows for causal interpretation of estimated effects of interventions or exposures using real-world observational data.…”
Section: Designmentioning
confidence: 99%